Assessment of fatigue, anxiety, depression and quality of life of women during radiotherapy (Research, Society and Development, 2022)
Objective: to identify the presence of fatigue, anxiety, depression and the health-related quality of life domains most affected in women during radiotherapy treatment. Methodology: a descriptive longitudinal study, carried out with women with gynecological and breast cancer undergoing radiotherapy at a university hospital. Data were collected from September/2018 to October/2019. The following were used: Piper Fatigue Scales, Hospital Anxiety and Depression Scale and Quality of Life Questionnaire-Core-30. Results: 13 women participated, predominantly over 40 years old and with cervical cancer. Regarding treatment, most underwent chemotherapy and cancer-related surgery, and most women underwent total mastectomy. Fatigue was reported by 15.4%; there was a significant increase in sensory fatigue between the times. The women were considered without anxiety and depression, even with an increase in the mean scores over time. The quality of life and its domains obtained satisfactory results between the times, while the role performance obtained a regular result. Loss of appetite, pain, nausea and vomiting, dyspnea and diarrhea were the most reported symptoms. Conclusion: despite the increase in the average scores of fatigue, anxiety and depression, they are considered of mild intensity. The quality of life had a drop in the average scores and the most reported symptoms were loss of appetite, pain, nausea and vomiting, dyspnea and diarrhea. Such complaints and symptoms require proper management, which is possible through holistic and humanized care.